A strong narrative and an improved outlook as a result of the growing order backlog – telecom and valuation - Maravalle, Giacomo (2021)
The following report is a subset of an Equity Research Report on Prysmian SpA completed by Giacomo Maravalle and Silvia La Barbera. It includes a brief description of the Telecom Business Unit, its respective market and long term drivers. It also discusses the results of the valuation and the underlying methodology.